Cambios recientes en el sector vitivinícola: el caso de las denominaciones de origen zaragozanas - Loscertales Palomar, Blanca; Escalona Orcao, Ana Isabel; Climent López, Eugenio (Geographicalia, 2014)
Wine industry has undergone important changes in last years concerning wine quality, production methods, markets and industrial organisation. In this article the response given by the three Protected Designations of Origin in the Zaragoza province (Cariñena, Campo de Borja and Calatayud) is analysed. They have addressed the production of great quality and singularity wines. First and second of them, with astrong productive network, have evolved positively, developing different production strategies (renovation versus tradition), while third, with a more atomised productive network, faces a strong adjustment process.